Pregnancy with inflammatory bowel disease: outcomes for mothers and their children at a European tertiary care center - Hoffmann, Peter; Krueger, Julian; Bashlekova, Teodora; Rupp, Christian; Baumann, Lukas; Gauss, Annika (The journal of obstetrics and gynaecology research, 2022)
Aim The study aimed at investigating pregnancy complications, birth outcomes, and postnatal child development in pregnancies of women with inflammatory bowel diseases (IBDs). Methods This is an uncontrolled retrospective single-center study between 2014 and 2019. It is a mixed-method cross-sectional study using data from (1) electronic patient records and (2) questionnaires and copies of mothers' and children's health booklets. Disease activity and IBD medications were analyzed and related to pregnancy complications, birth outcomes, and postnatal child development using mixed models for statistical analyses. Results Fifty live births from 46 patients were included. Disease activity anytime during pregnancy occurred in 56%. Biologics were applied in ca. 25% of pregnancies, mostly only through the second trimester. Pregnancies of mothers with active disease were slightly shorter than those of mothers with inactive disease (37.4 weeks vs. 38.9 weeks). Adverse pregnancy outcomes were reported in 28% of the live births, including small for gestational age in 6%, low birth weight in 18%, and preterm birth in 20%. Postnatal developmental abnormalities and health problems were reported in 26.8% of the children. Mixed model analyses failed to reveal significant associations between IBD activity and IBD medications during pregnancy and pregnancy complications, perinatal birth outcomes, and postnatal child development. Conclusion Despite a tendency of shorter pregnancies in patients with active IBD and lower birth weight and birth size in patients with IBD-related therapy during pregnancy, disease activity and medications did not significantly influence pregnancy, birth, and developmental outcomes.
First published: 21 December 2021
Gesehen am 24.04.2023